Philosophy, science and divine action - Murphy, Nancey C.; Russell, Robert J.; Shults, F. LeRon. (Philosophical Studies in Science and Religion, 2009)
One of the most important and controversial themes in the contemporary dialogue among scientists and Christian theologians is the issue of \'divine action\' in the world. This volume brings together contributions from leading scholars on this topic, which emerged out of the Scientific Perspectives on Divine Action project, co-sponsored by the Vatican Observatory and the Center for Theology and Natural Science. This multi-year collaboration involved over 50 authors meeting at five international conferences. The essays collected here demonstrate the pervasive role of philosophy in this dialogue. Contributors include: Ian Barbour, Philip Clayton, George F. R. Ellis, Nancey Murphy, Arthur Peacocke, John Polkinghorne, Robert John Russell, F. LeRon Shults, William Stoeger, Thomas F. Tracy and Wesley Wildman.